Stratigraphy of the area of Ukrainian Antarctic Akademik Vernadsky station - O. V. Mytrokhyn; V. G. Bakhmutov (Ukrainian Antarctic Journal, 2019)
In 2019 and 2017, the authors performed field geological research on the Graham Coast of the Antarctic Peninsula. The studied area covered the western coast of the Kiev Peninsula and most of the adjacent islands of the Wilhelm Archipelago. The main objective of the study was to specify the stratigraphic column for the Ukrainian Antarctic Station (UAS) area, to determine the petrographic composition and lithological features of strata, to find out the features of their occurrence and the succession of accumulation. Research methods included: large-scale geological surveying and geological mapping. The main result was the development of a new stratigraphic scheme for the UAS area. The authors found that the studied stratigraphic column was composed of volcanic and subordinate terrigenous deposits. Their accumulation lasted in the time interval from late Palaeozoic to Cenozoic inclusive. The conclusions have been made about to the origin of studied strata, their ages and possible analogues in neighbouring territories. Lahille Island Formation (LIF) was recognized as the oldest lithostratigraphic unit of the studied area. Deep-sea turbid origin is assumed for the LIF terrigenous rocks. The TTL sedimentation age is limited by the time interval between the Late Permian and Early Triassic periods. On the basis of lithological features and geological age, TTL correlates with the Paradise Harbour formation belonging to the Trinity Peninsula Group. The most widespread lithostratigraphic unit of the study area is the volcanic strata of the Kiev Peninsula, which is a product island-arc volcanism associated with the Andean orogeny. The age of KPF volcanism is defined as Jurassic. It is found that the volcanic stratum of the Argentine Islands Formation (AIF) differs from the KPF by the petrographic composition, occurrence and features of stratification. It gave grounds to separate AIF into an independent lithostratigraphic unite. The age of AIF volcanism is limited by the time interval between the Jurassic and Cretaceous periods. According to lithological features and geological age, KPF and AIF were identified as the members of Antarctic Peninsula Volcanic Group. An assumption about the possible presence of the latest volcanogenic rocks of Neogene or even Quaternary age on the Argentinean Islands is made.